Evaluation of the antiplasmodial properties of selected plants in southern Ethiopia. Issue 1 (December 2015) - Asnake, Solomon; Teklehaymanot, Tilahun; Hymete, Ariaya; Erko, Berhanu; Giday, Mirutse
Abstract Background The majority of the Ethiopian population is at risk of malaria largely caused byPlasmodium falciparum. The resistance of the parasite to existing drugs is the main challenge in the control of the disease and thus new therapeutic drugs are required. In Ethiopia, people use different plant species to treat malaria. However, very few of them have so far been evaluated for their safety level and antimalarial activity. Thus, the aim of this study was to evaluate the safety and antimalarial activity of extracts ofAjuga integrifolia, Clerodendrum myricoides, Melia azedarach, Peponium vogelii andPremna schimperi, locally used by the Sidama people of Ethiopia to treat malaria. Methods The safety level of 80 % methanol extracts of the plants were evaluated using standard acute toxicity test procedure. The antiplasmodial activity of 80 % methanol extracts of the plants were assessed in vivo using Swiss albino mice against chloroquine sensitive rodent malaria parasite, Plasmodium berghei, using the standard 4-day suppressive test procedure at doses of 200, 400 and 800 mg/kg/day. The 80 % methanol extract ofAjuga integrifolia that exhibited better antimalarial activity was fractionated using different solvents and screened for its phytochemical constituents and evaluated in vivo for its antimalarial activity at doses of 100, 200 and 400 mg/kg/day. Results All extracts given at the three different doses caused no lethal effect on mice in 24 h and within 10 days of observation. All extracts and fractions exhibited antimalarial activity in a dose dependant manner. The highest inhibition was exhibited by the crude extracts ofA. integrifolia (35.17 %) at 800 mg/kg/day (P < 0.05). Among fractions ofA. integrifolia, n-butanol fraction demonstrated the highest inhibition (29.80 %) at 400 mg/kg/day (P < 0.05). The extracts and fractions prolonged the survival time and prevented weight loss of the mice, but did not prevent PCV reduction. Phytochemical test onAjuga integrifolia indicated the presence of alkaloids, flavonoids, saponins, terpenoids, anthraquinone, steroids, tannins, phenols and fatty acids. Conclusions Findings show that the plants are non-toxic and demonstrate antimalarial activity in a dose dependant manner suporting claims of their traditional therapeutic value for malaria treatment. However, further in-depth investigation is required to assess the potential of the plants towards the development of new antimalarial agent.